Crisis Standards of Care: Ten Years of Successes and Challenges: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
In 2009 the Institute of Medicine (IOM) began to assess the need for better-defined medical and public health crisis standards of care (CSC) for catastrophic disasters and public health emergencies. Over the next 10 years, the IOM defined templates for those stakeholders responsible for integrated CSC planning and implementation; created a tool kit with guidance on indicators and triggers; provided a discussion kit for stakeholders to use with their own communities to establish appropriate indicators and triggers to guide their planning; disseminated the messages and key concepts of CSC; and built on the initial efforts to refine certain elements and address remaining gaps. This current Proceedings of a Workshop captures the discussions from a 2019 workshop reviewing the successes and gaps over the last 10 years of CSC work, in order to inform the next phases of planning and implementation.

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.

Crisis Standards of Care: A Systems Framework for Catastrophic Disaster Response: Volume 1: Introduction and CSC Framework - Institute of Medicine (The National Academies Press, 2012)
Catastrophic disasters occurring in 2011 in the United States and worldwide2014from the tornado in Joplin, Missouri, to the earthquake and tsunami in Japan, to the earthquake in New Zealand2014have demonstrated that even prepared communities can be overwhelmed. In 2009, at the height of the influenza A (H1N1) pandemic, the Assistant Secretary for Preparedness and Response at the Department of Health and Human Services, along with the Department of Veterans Affairs and the National Highway Traffic Safety Administration, asked the Institute of Medicine (IOM) to convene a committee of experts to develop national guidance for use by state and local public health officials and health-sector agencies and institutions in establishing and implementing standards of care that should apply in disaster situations-both naturally occurring and man-made-under conditions of scarce resources. Building on the work of phase one (which is described in IOM's 2009 letter report, Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations), the committee developed detailed templates enumerating the functions and tasks of the key stakeholder groups involved in crisis standards of care (CSC) planning, implementation, and public engagement-state and local governments, emergency medical services (EMS), hospitals and acute care facilities, and out-of-hospital and alternate care systems. Crisis Standards of Care provides a framework for a systems approach to the development and implementation of CSC plans, and addresses the legal issues and the ethical, palliative care, and mental health issues that agencies and organizations at each level of a disaster response should address. Please note: this report is not intended to be a detailed guide to emergency preparedness or disaster response. What is described in this report is an extrapolation of existing incident management practices and principles. Crisis Standards of Care is a seven-volume set: Volume 1 provides an overview; Volume 2 pertains to state and local governments; Volume 3 pertains to emergency medical services; Volume 4 pertains to hospitals and acute care facilities; Volume 5 pertains to out-of-hospital care and alternate care systems; Volume 6 contains a public engagement toolkit; and Volume 7 contains appendixes with additional resources.

Medical Surge Capacity: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
During natural disasters, disease pandemics, terrorist attacks, and other public health emergencies, the health system must be prepared to accommodate a surge in the number of individuals seeking medical help. For the health community, a primary concern is how to provide care to individuals during such high demand, when the health system's resources are exhausted and there are more patients than the system can accommodate. The IOM's Forum on Medical and Public Health Preparedness for Catastrophic Events held a workshop June 10-11, 2009, to assess the capability of and tools available to federal, state, and local governments to respond to a medical surge. In addition, participants discussed strategies for the public and private sectors to improve preparedness for such a surge. The workshop brought together leaders in the medical and public health preparedness fields, including policy makers from federal agencies and state and local public health departments; providers from the health care community; and health care and hospital administrators. This document summarizes the workshop.

Regional Disaster Response Coordination to Support Health Outcomes: Surge Management: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
When a disaster strikes, it rarely impacts just one jurisdiction. It is important for jurisdictions to consider how they will respond to a scenario in which the entire region is impacted. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required to ensure effective medical and public health response to a large-scale multijurisdictional disaster. Each of the three workshops covers different topics that may strengthen regional disaster response. The third and final workshop in this series, which this document summarizes, was held in New Orleans and considered how community engagement and information sharing can impact issues of surge management across the public health and health care spectrum.

The Public Health Emergency Medical Countermeasures Enterprise: Innovative Strategies to Enhance Products from Discovery Through Approval: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
During public health emergencies such as pandemic influenza outbreaks or terrorist attacks, effective vaccines, drugs, diagnostics, and other medical countermeasures are essential to protecting national security and the public's well-being. The Public Health Emergency Medical Countermeasures Enterprise (PHEMCE)–a partnership among federal, state, and local governments; industry; and academia–is at the forefront of the effort to develop and manufacture these countermeasures. However, despite the PHEMCE's many successes, there are still serious challenges to overcome. Government-funded medical research is not always focused on countermeasures for the most serious potential threats, and it is difficult to engage pharmaceutical and biotechnology companies to develop and manufacture medical countermeasures that have a limited commercial market. At the request of the Secretary of the U.S. Department of Health and Human Services and the Assistant Secretary for Preparedness and Response, the IOM held a workshop February 22-24, 2010, to address challenges facing the PHEMCE. Workshop participants discussed federal policies and procedures affecting the research, development, and approval of medical countermeasures and explored opportunities to improve the process and protect Americans' safety and health.

Preparedness and Response to a Rural Mass Casualty Incident: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Problems contacting emergency services and delayed assistance are not unusual when incidents occur in rural areas, and the consequences can be devastating, particularly with mass casualty incidents. The IOM's Forum on Medical and Public Health Preparedness for Catastrophic Events held a workshop to examine the current capabilities of emergency response systems and the future opportunities to improve mass casualty response in rural communities.

Preparedness, Response, and Recovery Considerations for Children and Families: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Preparedness, Response and Recovery Considerations for Children and Families is the summary of a workshop convened in June, 2013 by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events to discuss disaster preparedness, response, and resilience relative to the needs of children and families, including children with special health care needs. Traditional and non-traditional medical and public health stakeholders from across federal, state, and local government health care coalitions, community organizations, school districts, child care providers, hospitals, private health care providers, insurers, academia, and other partners in municipal planning met to review existing tools and frameworks that can be modified to include children's needs; identify child-serving partners and organizations that can be leveraged in planning to improve outcomes for children; highlight best practices in resilience and recovery strategies for children; and raise awareness of the need to integrate children's considerations throughout local and state emergency plans. Communities across the United States face the threat of emergencies and disasters almost every day, natural and man-made, urban and rural, large and small. Although children represent nearly 25 percent of the U.S. population, current state and local disaster preparedness plans often do not include specific considerations for children and families. The preparedness and resilience of communities related to children will require a systems framework for disaster preparedness across traditional and non-traditional medical and public health stakeholders, including community organizations, schools, and other partners in municipal planning. This report examines resilience strategies that lead to successful recovery in children after a disaster and discusses current approaches and interventions to improve recovery in children.

Regional Disaster Response Coordination to Support Health Outcomes: Information Sharing and Incident Management: Workshop in Brief - Institute of Medicine (The National Academies Press, 2014)
When a disaster strikes, it rarely impacts just one jurisdiction. It is important for jurisdictions to consider how they will respond to a scenario in which the entire region is impacted. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a workshop in 2014 to examine how information and incident management can augment response efforts in a complex, regional emergency. This brief summary highlights the presentation and discussion of the workshop.

Regional Disaster Response Coordination to Support Health Outcomes: Community Planning and Engagement: Workshop in Brief - Institute of Medicine (The National Academies Press, 2014)
Many catastrophic disaster plans include provisions of support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple groups and sectors together that don't routinely work with each other can augment a response to a disaster but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response.In March 2014, the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events convened a regional workshop bringing together key stakeholders to examine community planning and engagement when planning for health incidents in a large-scale response. This report highlights the presentations and discussion of that event.

Evolving Crisis Standards of Care and Ongoing Lessons from COVID-19: Proceedings of a Workshop Series - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Crisis Standards of Care (CSC) inform decisions on medical care during a large-scale crisis such as a pandemic or natural disaster, eliminating the need to make these decisions at the bedside without protections or guidance. Numerous points throughout the COVID-19 pandemic have demonstrated the necessity of this type of crisis planning. The National Academies of Sciences, Engineering, and Medicine Forum on Medical and Public Health Preparedness for Disasters and Emergencies convened a series of public workshops to examine the experiences of healthcare providers during the COVID-19 pandemic and identify lessons that can inform current and future CSC planning and implementation. The workshops examined staffing and workforce needs, planning and implementation of CSC plans, and legal, ethical, and equity considerations of CSC planning. Topics of discussion included improving coordination between the bedside and boardroom, increasing buy-in from elected officials, expanding provider engagement, and addressing health equity issues. This publication summarizes the presentation and discussion of the workshops.

Crisis Standards of Care: A Toolkit for Indicators and Triggers - Institute of Medicine (The National Academies Press, 2013)
Disasters and public health emergencies can stress health care systems to the breaking point and disrupt delivery of vital medical services. During such crises, hospitals and long-term care facilities may be without power; trained staff, ambulances, medical supplies and beds could be in short supply; and alternate care facilities may need to be used. Planning for these situations is necessary to provide the best possible health care during a crisis and, if needed, equitably allocate scarce resources. Crisis Standards of Care: A Toolkit for Indicators and Triggers examines indicators and triggers that guide the implementation of crisis standards of care and provides a discussion toolkit to help stakeholders establish indicators and triggers for their own communities. Together, indicators and triggers help guide operational decision making about providing care during public health and medical emergencies and disasters. Indicators and triggers represent the information and actions taken at specific thresholds that guide incident recognition, response, and recovery. This report discusses indicators and triggers for both a slow onset scenario, such as pandemic influenza, and a no-notice scenario, such as an earthquake. Crisis Standards of Care features discussion toolkits customized to help various stakeholders develop indicators and triggers for their own organizations, agencies, and jurisdictions. The toolkit contains scenarios, key questions, and examples of indicators, triggers, and tactics to help promote discussion. In addition to common elements designed to facilitate integrated planning, the toolkit contains chapters specifically customized for emergency management, public health, emergency medical services, hospital and acute care, and out-of-hospital care.

Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations: A Letter Report - Institute of Medicine (The National Academies Press, 2009)
The influenza pandemic caused by the 2009 H1N1 virus underscores the immediate and critical need to prepare for a public health emergency in which thousands, tens of thousands, or even hundreds of thousands of people suddenly seek and require medical care in communities across the United States. Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations draws from a broad spectrum of expertise2014including state and local public health, emergency medicine and response, primary care, nursing, palliative care, ethics, the law, behavioral health, and risk communication2014to offer guidance toward establishing standards of care that should apply to disaster situations, both naturally occurring and man-made, under conditions in which resources are scarce. This book explores two case studies that illustrate the application of the guidance and principles laid out in the report. One scenario focuses on a gradual-onset pandemic flu. The other scenario focuses on an earthquake and the particular issues that would arise during a no-notice event. Outlining current concepts and offering guidance, this book will prove an asset to state and local public health officials, health care facilities, and professionals in the development of systematic and comprehensive policies and protocols for standards of care in disasters when resources are scarce. In addition, the extensive operations section of the book provides guidance to clinicians, health care institutions, and state and local public health officials for how crisis standards of care should be implemented in a disaster situation.

Crisis Standards of Care: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2010)
During a wide-reaching catastrophic public health emergency or disaster, existing surge capacity plans may not be sufficient to enable health care providers to continue to adhere to normal treatment procedures and follow usual standards of care. This is a particular concern for emergencies that may severely strain resources across a large geographic area, such as a pandemic influenza or the detonation of a nuclear device. Under these circumstances, it may be impossible to provide care according to the standards of care used in non-disaster situations, and, under the most extreme circumstances, it may not even be possible to provide basic life sustaining interventions to all patients who need them. Although recent efforts to address these concerns have accomplished a tremendous amount in just a few years, a great deal remains to be done in even the most advanced plan. This workshop summary highlights the extensive work that is already occurring across the nation. Specifically, the book draws attention to existing federal, state, and local policies and protocols for crisis standards of care; discusses current barriers to increased provider and community engagement; relays examples of existing interstate collaborations; and presents workshop participants' ideas, comments, concerns, and potential solutions to some of the most difficult challenges.

Reusability of Facemasks During an Influenza Pandemic: Facing the Flu - Institute of Medicine (The National Academies Press, 2006)
Any strategy to cope with an influenza pandemic must be based on the knowledge and tools that are available at the time an epidemic may occur. In the near term, when we lack an adequate supply of vaccine and antiviral medication, strategies that rely on social distancing and physical barriers will be relatively more prominent as means to prevent spread of disease. The use of respirators and facemasks is one key part of a larger strategy to establish barriers and increase distance between infected and uninfected individuals. Respirators and facemasks may have a role in both clinical care and community settings. Reusability of Facemasks During an Influenza Pandemic: Facing the Flu answers a specific question about the role of respirators and facemasks to reduce the spread of flu: Can respirators and facemasks that are designed to be disposable be reused safely and effectively? The committee2014assisted by outstanding staff2014worked intensively to review the pertinent literature; consult with manufacturers, researchers, and medical specialists; and apply their expert judgment. This report offers findings and recommendations based on the evidence, pointing to actions that are appropriate now and to lines of research that can better inform future decisions.

Rapid Medical Countermeasure Response to Infectious Diseases: Enabling Sustainable Capabilities Through Ongoing Public- and Private-Sector Partnerships: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Emerging infectious disease threats that may not have available treatments or vaccines can directly affect the security of the world's health since these diseases also know no boundaries and will easily cross borders. Sustaining public and private investment in the development of medical countermeasures (MCMs) before an emerging infectious disease becomes a public health emergency in the United States has been extremely challenging. Interest and momentum peak during a crisis and wane between events, and there is little interest in disease threats outside the United States until they impact people stateside. On March 26 and 27, 2015, the Institute of Medicine convened a workshop in Washington, DC to discuss how to achieve rapid and nimble MCM capability for new and emerging threats. Public- and private-sector stakeholders examined recent efforts to prepare for and respond to outbreaks of Ebola Virus Disease, pandemic influenza, and coronaviruses from policy, budget, and operational standpoints. Participants discussed the need for rapid access to MCM to ensure national security and considered strategies and business models that could enhance stakeholder interest and investment in sustainable response capabilities. This report summarizes the presentations and discussions from this workshop.

Engaging the Public in Critical Disaster Planning and Decision Making: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Engaging the Public in Critical Disaster Planning and Decision Making is the summary of a workshop held in March 2013 to discuss the key principles of public engagement during the development of disaster plans, the response phase, and during the dissemination phase when interested community partners and the general public are informed of the policies that have been adopted. Presenters provided specific examples of resources to assist jurisdictions in planning public engagement activities as well as challenges experienced and potential solutions. This report introduces key principles of public engagement, provides practical guidance on how to plan and implement a public engagement activity, and presents tools to facilitate planning.

Barriers to Integrating Crisis Standards of Care Principles into International Disaster Response Plans: Workshop Summary - Institute of Medicine (The National Academies Press, 2012)
When a nation or region prepares for public health emergencies such as a pandemic influenza, a large-scale earthquake, or any major disaster scenario in which the health system may be destroyed or stressed to its limits, it is important to describe how standards of care would change due to shortages of critical resources. At the 17th World Congress on Disaster and Emergency Medicine, the IOM Forum on Medical and Public Health Preparedness sponsored a session that focused on the promise of and challenges to integrating crisis standards of care principles into international disaster response plans.